2016
DOI: 10.1002/2016ja022375
|View full text |Cite
|
Sign up to set email alerts
|

Global images of trapped ring current ions during main phase of 17 March 2015 geomagnetic storm as observed by TWINS

Abstract: A unique view of the trapped particles in the inner magnetosphere provided by energetic neutral atom (ENA) imaging is used to observe the dynamics of the spatial structure and the pitch angle anisotropy on a global scale during the last 6 h of the main phase of a large geomagnetic storm (minimum SYM‐H = −230 nT) that began on 17 March 2015. Ion flux and pressure anisotropy obtained from Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS) ENA images are shown. The ion flux shows two peaks, an inner one at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…Orbits/locations of RBSP (A and B) and THEMIS (a, d, and e) are overplotted together. Added to Figure c is a map of TWINS 1 ion flux, obtained via numerical inversion [ Perez et al , , ] from the nearest‐in‐time (1645 UT) ENA image. The TWINS inversion map shows 15 keV pitch angle‐averaged equatorial flux in units of log10(normalcm20.3emnormalsr0.3emnormals0.3emnormaleV)1, as given by the colorbar at the bottom right.…”
Section: Ring Current Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Orbits/locations of RBSP (A and B) and THEMIS (a, d, and e) are overplotted together. Added to Figure c is a map of TWINS 1 ion flux, obtained via numerical inversion [ Perez et al , , ] from the nearest‐in‐time (1645 UT) ENA image. The TWINS inversion map shows 15 keV pitch angle‐averaged equatorial flux in units of log10(normalcm20.3emnormalsr0.3emnormals0.3emnormaleV)1, as given by the colorbar at the bottom right.…”
Section: Ring Current Dynamicsmentioning
confidence: 99%
“…Indeed, fluxes measured by a different instrument (Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE)) on the same spacecraft (RBSP A), obtained during the same 17 March storm, are significantly lower than those measured simultaneously by HOPE. For example, between 1700 and 1715 UT RBSPICE A measured a peak 30 keV flux of ∼300 (cm 2 srseV) −1 [ Perez et al , ]. In the same interval, HOPE A recorded a mean 30 keV flux of 6 × 10 3 (cm 2 srseV) −1 , i.e., >20 times higher flux.…”
Section: Ring Current Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the global‐local agreement in Figure b, Perez et al () had demonstrated that stereo imaging more accurately resolves flux peaks. The newer result by Perez et al (), using only TWINS 1, shows how single‐point inversions can still achieve reasonable agreement—in both flux and PAD—with in situ data.…”
Section: Scientific Results From 2013 To 2017mentioning
confidence: 93%
“…Current inversion and forward modeling techniques from ENA images do not fully utilize LAE signatures and MCCIs effects (Brandt et al, ; Perez et al, ; Roelof & Skinner, ; Vallat et al, ). These midlatitude to high‐latitude LAEs (dominant ENA signatures from prestorm through main phase (i.e., Valek et al, , )) include plasma sheet particles mapping farther down into the magnetotail, as shown in Perez et al (). Our model allows us to apply these findings to interpret observations where MCCIs are involved, maximizing the particle information that can be retrieved by global ENA images.…”
Section: Discussionmentioning
confidence: 99%